Meningkatkan Kualitas Pendidikan di Sekolah dengan Pendekatan Sistem Menyelaraskan Struktur, Proses, dan Sumber Daya - Amiruddin, Amiruddin; Ahmad, Amar Khairi; Ramadani, Intan; Zuraira, Tasya (MODELING: Jurnal Program Studi PGMI, 2023)
The system approach is one of the approaches that schools can use to improve education quality and achieve the goals that have been set. This approach emphasizes the importance of aligning all education components, including organizational structure, teaching and learning processes, and available resources, to achieve more effective performance. This article will discuss how the system approach can be used in schools to improve education quality, by providing case studies that describe how this approach has been successfully implemented in schools in various countries. In addition, this article will also discuss the challenges that may be faced in implementing the system approach in schools and ways to overcome them.